A comparative analysis of the effects of landfills on water quality: a case study of two locations in New Jersey - Saavedra, Casilda (Universidad Tecnológica de Panamá, 2019)
Leachate is a liquid generated by mixing of water with organic and inorganic material found in landfills. This liquid accumulates at the bottom of the landfill and has the potential to percolate through the soil to enter groundwater or other water bodies. Leachate contains various contaminants and toxins that can significantly diminish the quality of water it enters, which can become hazardous to humans and the environment. In this article, the water quality of two towns: Egg Harbor and Middle Township, New Jersey were analyzed and compared. Egg Harbor Township has a landfill located within the town, while the closest landfill to Middle Township is approximately 10 miles away. Water supply for both towns comes from the same aquifer, known as the Kirkwood-Cohansey water table system. The water quality results from community wells within Egg Harbor Township were compared to those of Middle Township. Water quality data for this study is from New Jersey American Water database. Based on the results, the water quality of Egg Harbor Township varies significantly from Middle Township. The levels of contaminants in Egg Harbor Township are much higher compared to Middle Township. Therefore, it can be concluded that communities near landfills, even well monitored and managed ones, are prone to have poorer water quality than those farther away from the landfill.